In vivo brain temperature mapping using polymer optical fiber Bragg grating sensors - Sui, Kunyang; Meneghetti, Marcello; Guanghui, Li; Ioannou, Andreas; Abdollahian, Parinaz; Kalli, Kyriacos; Nielsen, Kristian; Berg, Rune W; Markos, Christos (My University, 2023)
Variation of the brain temperature is strongly affected by blood flow, oxygen supply, and neural cell metabolism. Localized monitoring of the brain temperature is one of the most effective ways to correlate brain functions and diseases such as stroke, epilepsy, and mood disorders. While polymer optical fibers (POFs) are considered ideal candidates for temperature sensing in the brain, they have never been used so far in vivo. Here, we developed for the first, to the best of our knowledge, time an implantable probe based on a microstructured polymer optical fiber Bragg grating (FBG) sensor for intracranial brain temperature mapping. The temperature at different depths of the brain (starting from the cerebral cortex) and the correlation between the brain and body core temperature of a rat were recorded with a sensitivity of 33 pm/°C and accuracy <0.2°C. Our in vivo experimental results suggest that the proposed device can achieve real-time and high-resolution local temperature measurement in the brain, as well as being integrated with existing neural interfaces.
Keywords: Animals; Brain; Optical Fibers; Polymers; Rats; Temperature; Thermography